Extracellular matrix of secondary lymphoid organs impacts on B-cell fate and survival - Song, Jian; Lokmic, Zerina; Laemmermann, Tim; Rolf, Julia; Wu, Chuan; Zhang, Xueli; Hallmann, Rupert; Hannocks, Melanie-Jane; Horn, Nathalie; Ruegg, Markus A.; Sonnenberg, Arnoud; Georges-Labouesse, Elisabeth; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
We describe a unique extracellular matrix (ECM) niche in the spleen, the marginal zone (MZ), characterized by the basement membrane glycoproteins, laminin α5 and agrin, that promotes formation of a specialized population of MZ B lymphocytes that respond rapidly to blood-borne antigens. Mice with reduced laminin α5 expression show reduced MZ B cells and increased numbers of newly formed (NF) transitional B cells that migrate from the bone marrow, without changes in other immune or stromal cell compartments. Transient integrin α6β1-mediated interaction of NF B cells with laminin α5 in the MZ supports the MZ B-cell population, their long-term survival, and antibody response. Data suggest that the unique 3D structure and biochemical composition of the ECM of lymphoid organs impacts on immune cell fate. © PNAS 2013.
Keywords: B-cell development; Immunology